2018
DOI: 10.7150/thno.23686
|View full text |Cite
|
Sign up to set email alerts
|

A large, switchable optical clearing skull window for cerebrovascular imaging

Abstract: Rationale: Intravital optical imaging is a significant method for investigating cerebrovascular structure and function. However, its imaging contrast and depth are limited by the turbid skull. Tissue optical clearing has a great potential for solving this problem. Our goal was to develop a transparent skull window, without performing a craniotomy, for use in assessing cerebrovascular structure and function.Methods: Skull optical clearing agents were topically applied to the skulls of mice to create a transpare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
89
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 82 publications
(91 citation statements)
references
References 49 publications
0
89
0
2
Order By: Relevance
“…In this work, another important approach for minimizing negative consequences of PDT effects to the brain vasculature and tissues is the application of the skull optical clearing technique [32,52,53]. Generally, PDT performance requires a craniotomy in both clinical and fundamental studies due to the high scattering property of the skull, which leads to low light penetration into the brain [7,9,10,[54][55][56].…”
Section: Discussionmentioning
confidence: 99%
“…In this work, another important approach for minimizing negative consequences of PDT effects to the brain vasculature and tissues is the application of the skull optical clearing technique [32,52,53]. Generally, PDT performance requires a craniotomy in both clinical and fundamental studies due to the high scattering property of the skull, which leads to low light penetration into the brain [7,9,10,[54][55][56].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it is necessary to differentiate water control in skin layers on the short (minutes) and long (hours and days) time scales. For effective OC, it is possible to provide fast, strong and reversible skin dehydration for tissue in‐depth laser probing aiming at diagnostics, therapy or theranostics . This can be done by using highly concentrated OCAs together with enhancers of skin permeability .…”
Section: Introductionmentioning
confidence: 99%
“…Creating novel windows for brain studies has been gaining attention recently 35,[76][77][78] . Some of these studies, involving OCAs applied to the scalp overlying native skull, have shown limited success due to optical losses and scattering in the skull 32 . Future studies by our group will explore this combined OCA-WttB strategy for chronic imaging in awake and behaving animals through closed scalp, to study cerebrovascular hemodynamic responses to a photoactivation stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the optical properties of the inhomogeneous cranial bone overlap with those of brain tissue and jointly these factors decrease the accuracy and reliability of the data. Studies in the literature have addressed this optical barrier with various approaches including imaging the brain directly with an opened skull 28 , thinned and polished skull preparations 29,30 , temporary optical clearing of the skull using optical clearing agents [31][32][33] , and implanting glass or PDMS windows 34,35 . Glass and PDMS windows are powerful research techniques, but are not appropriate for human application as permanent cranial implants for patients.…”
Section: Introductionmentioning
confidence: 99%